Resistive-Switching Behavior in Polycrystalline CaCu3Ti4O12 Nanorods - Tararam, R. [UNESP]; Joanni, E.; Savu, R.; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Amer Chemical Soc, 2011)
Highly aligned CaCu3Ti4O12 nanorod arrays were grown on Si/SiO2/Ti/Pt substrates by radio-frequency sputtering at a low deposition temperature of 300 degrees C and room temperature. Structural and morphological studies have shown that the nanostructures have a polycrystalline nature and are oriented perpendicular to the substrate. The high density of grain boundaries in the nanorods is responsible for the nonlinear current behavior observed in these arrays. The current-voltage (I-V) characteristics observed in nanorods were attributed to the resistive memory phenomenon. The electrical resistance of microcapacitors composed of CaCu3Ti4O12 nanorods could be reversibly switched between two stable resistance states by varying the applied electric field. In order to explain this switching mechanism, a model based on the increase/decrease of electrical conduction controlled by grain boundary polarization has been proposed.
Keywords: CCTO; nanorods; dielectric; nonlinear I-V; resistive switching; RF sputtering